Preserved imitation in contrast to limited free application of comfortable hand actions in intellectually able young adults with an autism spectrum disorder. (August 2018) - Beelen, Caroline; Cuypers, Koen; van Schuerbeeck, Lise; Braeken, Marijke; Ross, Veerle; Jongen, Ellen; Meesen, Raf; Vanvuchelen, Marleen
Imitation problems are commonly reported in children with an autism spectrum disorder. However, it has not yet been determined whether imitation problems persist into young adulthood. In this study, we investigated imitation skills of 20 intellectually able young adults with autism spectrum disorder relative to 19 age-matched neurotypical adults. For this purpose, we used a bar-transport task, which evokes the application of the end-state comfort principle. Specifically, we examined whether young adults with autism spectrum disorder imitated the means-end structure of a demonstrator's bar-transport action with and without application of the end-state comfort principle (imitation task). In addition, we examined whether participants spontaneously applied the end-state comfort principle during a similar bar-transport task (free execution task). Results revealed that young adults with autism spectrum disorder imitated the means-end structure of observed actions to the same degree as neurotypical adults ( p = 0.428). In contrast, they applied the end-state comfort principle less often during free executed actions ( p = 0.035). Moreover, during these actions, they were slower to place the bar into the penholder ( p = 0.023), which contributed to the reduced efficiency of their performance. Findings suggest that imitation abilities of young adults with autism spectrum disorder are preserved and that observing others' actions might promote more efficient action planning in this population.